Voltammetric sensing of tryptophan in dark chocolate bars, skimmed milk and urine samples in the presence of dopamine and caffeine - Wong, Ademar [UNESP]; Materón, Elsa María; Freitas, Tayane A.; Faria, Ronaldo C.; Gonçalves, Débora; Sotomayor, Maria Del Pilar Taboada [UNESP] (Springer Nature, 2022)
The present work reports the development of screen-printed electrode (SPE) using flexible polyester sheets modified with nanodiamond (ND), Au nanoparticles (AuNPs), and poly(3,4-ethylene dioxythiophene):polystyrene sulfonate (PEDOT:PSS), and its application for the detection of tryptophan in synthetic urine, milk, and dark chocolate samples. The ND/AuNPs/PEDOT:PSS nanocomposite was characterized by cyclic voltammetry, scanning electron microscopy and energy-dispersive X-ray spectroscopy. The proposed ND/AuNPs/PEDOT:PSS-based SPE was applied for the detection of tryptophan using square-wave voltammetry in a linear detection range of 0.8 µmol L−1–18 µmol L−1, with limits of detection (LOD) and quantification (LOQ) of 0.2 µmol L−1 and 0.8 µmol L−1, respectively. The sensor was successfully applied for tryptophan quantification in dark chocolate, milk and synthetic urine where good recovery percentages were obtained. The results obtained from the analysis of interference in the presence of dopamine and caffeine showed that the ND/AuNPs/PEDOT:PSS-based SPE exhibited excellent selectivity toward tryptophan. The findings of this study show that metallic nanoparticles, nanodiamonds and biocompatible conductive composites can be used as a suitable, affordable alternative tool for fast, simple, and low-cost detection of tryptophan in non-invasive testing and analysis of food products. Graphical abstract: [Figure not available: see fulltext.]
Keywords: Electrochemical sensors; Metallic nanoparticles; Nanodiamond; Screen-printed electrodes; Tryptophan